Negative oxygen ion functional granular ball and preparation method and application thereof

By developing negative oxygen ion functional particle balls, using modified self-polarized composite materials and waste concave and concave rock stones and other materials, low-energy consumption and high efficiency air purification is achieved, solving the problems of high energy consumption and high cost in the existing technology, and maintaining long-term effects in various environments.

CN119746806AInactive Publication Date: 2025-04-04朱鸿亮
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510042054.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing air purification technology has problems such as high energy consumption, high cost, inconvenient maintenance and low purification effect. Especially when using negative oxygen ions to purify air, electricity and complex equipment are required, resulting in high efficiency and cost.

Method used

A negative oxygen ion functional particle ball was developed to prepare modified self-polarized composite materials by mixing bentonite, lithium carbonate and gypsum, and combining waste concave and concave rock stone, rare earth elements and tourmaline powder, and prepare particle balls in pure physical ways, which can continuously produce high concentrations of negative oxygen ions in the long run.

Benefits of technology

It realizes air purification with low energy consumption, high purification efficiency, long-lasting effect and not limited by light conditions. It can effectively suppress and eliminate harmful gases such as formaldehyde, and maintain a long service life in humid and dry environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746806A_ABST
    Figure CN119746806A_ABST
Patent Text Reader

Abstract

The invention provides a negative oxygen ion functional granular ball and a preparation method and application thereof, belonging to the technical field of air purification; the invention prepares a negative oxygen ion functional granular ball by mixing a modified self-polarizing composite material, modified attapulgite, rare earth elements and tourmaline powder; prepares a modified self-polarizing composite material by mixing bentonite, lithium carbonate and gypsum; prepares oxidized attapulgite by oxidizing and calcining discarded attapulgite in a muffle furnace, and prepares modified attapulgite by mixing oxidized attapulgite and a modifier; the negative oxygen ion functional granular ball prepared by the invention can continuously generate high-concentration negative oxygen ions for more than 10 years, and effectively inhibit and eliminate harmful gases such as formaldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of air purification, and in particular to a negative oxygen ion functional granular ball and a preparation method and application thereof. Background Art

[0002] For a long time, it has been a difficult problem to quickly, persistently and effectively eliminate harmful gases such as formaldehyde, benzene, viruses, bacteria, odors, etc. in indoor and car environments. Air purification technology is a technology and method used to remove pollutants and impurities in indoor or outdoor air to improve air quality. Therefore, it is of great significance to develop efficient and environmentally friendly air purification technology.

[0003] There are some existing technologies for purifying the air, such as activated carbon adsorption, photocatalytic oxidation, ultraviolet light disinfection, nano-photocatalysts, etc. However, these technologies usually have problems such as low purification effect, high energy consumption, high cost, and limited purification environment.

[0004] Negative oxygen ion functional granules are a type of material that uses negative oxygen ions to purify the air. Negative oxygen ions are negatively charged oxygen atoms that have a variety of biological activities and chemical properties. In the air, negative oxygen ions can react with harmful substances such as pollutants and bacteria, making them inactive or neutralized, thereby achieving the purpose of purifying the air. At present, there are some technologies that use negative oxygen ions to purify the air, such as negative oxygen ion generators, negative oxygen ion purifiers, etc. However, these technologies usually require the use of electricity or complex equipment to generate negative oxygen ions, and have problems such as high energy consumption, high cost, and inconvenient maintenance.

[0005] Therefore, it is of great significance to provide a negative oxygen ion air purification material with low energy consumption, high purification efficiency, long-lasting purification effect, and no restrictions on light conditions. Summary of the invention

[0006] Based on the deficiencies of the prior art, the present invention provides a negative oxygen ion functional granular ball and a preparation method and application thereof, which specifically include the following contents.

[0007] The invention provides a negative oxygen ion functional granular ball, characterized in that it comprises a surface material and an internal material.

[0008] Preferably, the surface layer material comprises a modified self-polarizing composite material.

[0009] Preferably, the inner material comprises a mineral material with permanent electrodes and an ultra-fine mesh mineral clay.

[0010] Preferably, the mineral material with permanent electrodes is tourmaline powder.

[0011] Preferably, the modified self-polarizing composite material is prepared by a mixed reaction of bentonite, lithium carbonate and gypsum.

[0012] Preferably, the ultrafine mesh mineral clay comprises modified attapulgite and rare earth elements.

[0013] Preferably, the rare earth element is at least one of cerium oxide, neodymium oxide and lanthanum oxide.

[0014] Preferably, the modified attapulgite is prepared by a mixed reaction of oxidized attapulgite and a modifier.

[0015] Preferably, the oxidized attapulgite is prepared by oxidative calcination of waste attapulgite in a muffle furnace.

[0016] Preferably, the modifier comprises at least one of octadecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, and phenyltripropylammonium bromide.

[0017] The present invention also provides a method for preparing negative oxygen ion functional granular balls, comprising the following steps:

[0018] Step 1, prepare materials: weigh the modified self-polarized composite material, modified attapulgite, rare earth element, and tourmaline powder in a weight ratio of 40-50:30-40:10-20:20-30 and set aside;

[0019] Step 2: After mixing tourmaline powder, modified attapulgite and rare earth elements, put them into a ball rolling machine, spray water mist into the ball rolling machine to form primary particles first, and start the next step after the particles reach a particle size of 3 to 4 mm;

[0020] Step 3: Add the modified self-polarized composite material into the ball rolling machine, spray water mist into the ball rolling machine, and start the next step after the particles reach 5-7 mm;

[0021] Step 4: Dry the particles obtained in step 3 under natural conditions for 24 to 48 hours, then put them into an autoclave for steam curing at 180 to 200° C. for 20 to 24 hours, and dry them to obtain a negative oxygen ion functional particle ball.

[0022] Preferably, the preparation method of the modified self-polarized composite material is as follows:

[0023] 1) Mixing bentonite, lithium carbonate and gypsum in a mass ratio of 20-30:10:30-40 to obtain a mixed material;

[0024] 2) adding the mixed material, zirconium oxide ball milling beads and water into a ball mill at a mass ratio of 1:1.2-1.7:0.5-0.8, and ball milling for 4-5 hours. The ball-milled material is placed in a forced air drying oven at 70-90° C. for 12-24 hours to remove moisture from the mixed material, and passed through a 100-mesh sieve to obtain an intermediate 1;

[0025] 3) adding the intermediate 1 and polyvinyl pyrrolidone into a corundum crucible at a mass ratio of 1000:3-5, and calcining at 700-750° C. for 3-4 hours to obtain a modified self-polarized composite material.

[0026] Preferably, the preparation method of the modified attapulgite is as follows:

[0027] S1, placing the waste attapulgite in a muffle furnace for oxidation calcination at a temperature of 550-600° C. for 1-2 h, then crushing it with a high-speed universal crusher for 15-30 seconds, passing it through a 100-mesh sieve, and obtaining oxidized attapulgite;

[0028] S2. Mix oxidized attapulgite, ethanol and deionized water in a mass ratio of 10:150-200:150-200, stir magnetically for 15-30 min, add a modifier, adjust the temperature to 60°C, stir with a constant temperature magnetic stirrer for 12-15 h, filter after stirring, wash the filter residue with ethanol and deionized water, put it into an oven, and dry it at 40-50°C for 30-60 min to obtain modified attapulgite.

[0029] The present invention also provides an application of the negative oxygen ion functional granular ball described in claim 1 in purifying indoor air and purifying the air in a car.

[0030] Preferably, in the application, the reaction process of the negative oxygen ion functional granule ball ionizing negative ions in the air is:

[0031] H2O→OH - +H +

[0032] 2H + +2e - →H2

[0033] OH - +H2O→H30 -

[0034] O2+e - →O2 - .

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present invention prepares a modified self-polarizing composite material by mixing bentonite, lithium carbonate and gypsum, prepares oxidized attapulgite by oxidative calcination of discarded attapulgite in a muffle furnace, prepares modified attapulgite by mixing oxidized attapulgite and a modifier, and prepares a negative oxygen ion functional granular ball by mixing the modified self-polarizing composite material, modified attapulgite, rare earth elements and tourmaline powder. The granular ball can continuously generate high concentrations of negative oxygen ions for more than 10 years, effectively inhibiting and eliminating harmful gases such as formaldehyde.

[0037] (2) The present invention recycles waste attapulgite to achieve resource recycling and save production costs; the attapulgite is modified to have hydrophobic properties. As the internal material of the negative oxygen ion functional granule, it can prevent outer moisture from entering the interior, causing the tourmaline to get damp and affecting the ionization ability of the tourmaline; bentonite, lithium carbonate, and gypsum are prepared into a modified self-polarizing composite material with excellent polarization ability, which can release a large amount of negative ions for ionization in the air; gypsum has a water-retaining effect, which can provide sufficient raw materials for the negative oxygen ion functional granule to ionize water molecules; the outer layer has water-retaining properties, and the inner layer has hydrophobic properties. The two parts interact with each other, so that the negative oxygen ion functional granule has a high air purification efficiency and a long service life in both humid and dry environments.

[0038] (3) The negative oxygen ion functional granule ball prepared by the present invention adopts a purely physical method, which can continuously produce high-concentration negative oxygen ions for more than 10 years, effectively inhibit and eliminate the above-mentioned harmful gases, and generate electric charges and millivolt potential energy under the influence of temperature, infrared rays, air pressure, and geomagnetism, thereby generating an electrostatic field around the crystal. When the electric field intensity exceeds the millivolt ionization threshold of water molecules, the water molecules can be ionized. The surface of the granule ball is covered with a film to form a solidified porous structure. When the water molecules in the air approach the polar crystals in the coating film, they will be ionized into hydroxide ions and hydrogen ions by the electric field, among which H + After grounding and gaining electrons, it turns into hydrogen molecules and escapes, and the remaining OH - It escapes into the air and combines with oxygen molecules and water molecules in the air to form negatively charged hydrated hydroxyl ions, which are negative oxygen ions. This cycle is repeated, thereby increasing the concentration of negative ions in the air and achieving the purpose of improving the environment.

[0039] (4) The negative ion granules prepared by the present invention contain mineral materials with permanent electrodes. When exposed to ambient temperature and light, they will obtain higher potential energy. When water molecules and oxygen molecules in the air approach the self-polar materials, they will be ionized to generate OH - and H + , due to H + It can absorb an e from zero potential mineral materials with permanent electrodes and ultrafine mineral clays.- becomes H2 and escapes into the air, while OH - It forms H3O2 with other water molecules - Through this reaction, the polar material in the negative ion particle ball transfers its own negative charge to the air, forming O2 - , H3O2 - It becomes negative oxygen ions, and the electron loss of the polar material is promptly replenished by the mineral material with permanent electrodes in the ball, and this process is repeated to continuously release negative ions.

[0040] (5) Compared with activated carbon adsorption, the present invention can not only inhibit and eliminate harmful gases and odors, but also achieve active purification by continuously generating negative oxygen ions; compared with air purifiers, the present invention does not require continuous power consumption and can deal with pollution inside furniture; compared with ultraviolet light disinfection, the present invention can not only sterilize and disinfect, but also degrade pollutants to create a healthier indoor environment; compared with negative ion generators, the present invention does not require the use of electrical equipment and continuous power consumption, and continuously generates high-concentration negative oxygen ions within 24 hours through a purely physical method, and the effect is more lasting; compared with nano photocatalysts, the present invention is not limited by light conditions and can work effectively in various environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The present invention is a flow chart for preparing a negative oxygen ion functional granular ball. DETAILED DESCRIPTION

[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] This embodiment provides a method for preparing negative oxygen ion functional granular balls

[0045] 1. Preparation of modified attapulgite:

[0046] S1. The waste attapulgite is placed in a muffle furnace for oxidation calcination at a temperature of 600° C. for 2 h, and then crushed with a high-speed universal crusher for 15 seconds and passed through a 100-mesh sieve to obtain oxidized attapulgite.

[0047] S2. Mix oxidized attapulgite, ethanol and deionized water in a mass ratio of 10:200:200, stir magnetically for 15 minutes, add a modifier, adjust the temperature to 60°C, stir with a constant temperature magnetic stirrer for 12 hours, filter after stirring, wash the filter residue with ethanol and deionized water, put it into an oven, and dry it at 50°C for 60 minutes to obtain modified attapulgite.

[0048] 2. Preparation of modified self-polarized composite materials:

[0049] 1) Mixing bentonite, lithium carbonate and gypsum in a mass ratio of 30:10:40 to obtain a mixed material;

[0050] 2) The mixed material, zirconium oxide ball milling beads and water were added into a ball mill at a mass ratio of 1:1.2:0.8, and the ball milled material was placed in a forced air drying oven at 90°C for 12 hours to remove moisture in the mixed material, and passed through a 100 mesh sieve to obtain an intermediate 1;

[0051] 3) The intermediate 1 and polyvinyl pyrrolidone were added into a corundum crucible in a mass ratio of 1000:3, and calcined at 700° C. for 4 h to obtain a modified self-polarized composite material.

[0052] 3. Preparation of negative oxygen ion functional granular balls:

[0053] Step 1, weighing the modified self-polarized composite material, modified attapulgite, rare earth element, and tourmaline powder in a weight ratio of 40:30:10:20 for standby use;

[0054] Step 2: After mixing tourmaline powder, modified attapulgite and rare earth elements, put them into a ball rolling machine, spray water mist into the ball rolling machine to form primary particles first, and start the next step after the particles reach a particle size of 3 mm;

[0055] Step 3: Add the modified self-polarized composite material into the ball rolling machine, spray water mist into the ball rolling machine, and start the next step after the particles reach 5mm;

[0056] Step 4: Dry the particles obtained in step 3 under natural conditions for 24 hours, then put them into an autoclave for steam curing at 200° C. for 24 hours, and dry them to obtain a negative oxygen ion functional particle ball.

[0057] Example 2

[0058] This embodiment provides a method for preparing negative oxygen ion functional granular balls

[0059] 1. Preparation of modified attapulgite:

[0060] S1. The waste attapulgite is placed in a muffle furnace for oxidation calcination at a temperature of 550° C. for 1 h, and then crushed with a high-speed universal crusher for 15 seconds and passed through a 100-mesh sieve to obtain oxidized attapulgite.

[0061] S2. Mix oxidized attapulgite, ethanol and deionized water in a mass ratio of 10:150:150, stir magnetically for 15 minutes, add a modifier, adjust the temperature to 60°C, stir with a constant temperature magnetic stirrer for 12 hours, filter after stirring, wash the filter residue with ethanol and deionized water, put it into an oven, and dry it at 50°C for 30 minutes to obtain modified attapulgite.

[0062] 2. Preparation of modified self-polarized composite materials:

[0063] 1) Mixing bentonite, lithium carbonate and gypsum in a mass ratio of 30:10:40 to obtain a mixed material;

[0064] 2) adding the mixed material, zirconium oxide ball milling beads and water in a mass ratio of 1:1.2:0.5 into a ball mill and milling for 4 hours. The milled material is placed in a forced air drying oven at 70°C for 24 hours to remove moisture from the mixed material, and passed through a 100-mesh sieve to obtain an intermediate 1;

[0065] 3) The intermediate 1 and polyvinyl pyrrolidone were added into a corundum crucible at a mass ratio of 1000:3, and calcined at 750° C. for 3 h to obtain a modified self-polarized composite material.

[0066] 3. Preparation of negative oxygen ion functional granular balls:

[0067] Step 1, weighing the modified self-polarized composite material, modified attapulgite, rare earth element, and tourmaline powder in a weight ratio of 40:30:10:20 for standby use;

[0068] Step 2: After mixing tourmaline powder, modified attapulgite and rare earth elements, put them into a ball rolling machine, spray water mist into the ball rolling machine to form primary particles first, and start the next step after the particles reach a particle size of 3 mm;

[0069] Step 3: Add the modified self-polarized composite material into the ball rolling machine, spray water mist into the ball rolling machine, and start the next step after the particles reach 5mm;

[0070] Step 4: Dry the particles obtained in step 3 under natural conditions for 48 hours, then put them into an autoclave for steam curing at 180-200° C. for 20 hours, and dry them to obtain a negative oxygen ion functional particle ball.

[0071] Example 3

[0072] This embodiment provides a method for preparing negative oxygen ion functional granular balls

[0073] 1. Preparation of modified attapulgite:

[0074] S1. The waste attapulgite is placed in a muffle furnace for oxidation calcination at a temperature of 600° C. for 2 h, and then crushed with a high-speed universal crusher for 30 seconds and passed through a 100-mesh sieve to obtain oxidized attapulgite.

[0075] S2. Mix oxidized attapulgite, ethanol and deionized water in a mass ratio of 10:200:200, stir magnetically for 15 minutes, add a modifier, adjust the temperature to 60°C, stir with a constant temperature magnetic stirrer for 15 hours, filter after stirring, wash the filter residue with ethanol and deionized water, put it into an oven, and dry it at a temperature of 40-50°C for 30 minutes to obtain modified attapulgite.

[0076] 2. Preparation of modified self-polarized composite materials:

[0077] 1) Mixing bentonite, lithium carbonate and gypsum in a mass ratio of 30:10:40 to obtain a mixed material;

[0078] 2) adding the mixed material, zirconium oxide ball milling beads and water into a ball mill at a mass ratio of 1:1.2:0.5, and ball milling for 5 hours. The ball-milled material was placed in a forced air drying oven at 80° C. for 12 hours to remove moisture from the mixed material, and passed through a 100-mesh sieve to obtain an intermediate 1;

[0079] 3) The intermediate 1 and polyvinyl pyrrolidone were added into a corundum crucible at a mass ratio of 1000:5, and calcined at 750° C. for 4 h to obtain a modified self-polarized composite material.

[0080] 3. Preparation of negative oxygen ion functional granular balls:

[0081] Step 1, weighing the modified self-polarized composite material, modified attapulgite, rare earth element, and tourmaline powder in a weight ratio of 50:40:20:30 and setting aside;

[0082] Step 2: After mixing tourmaline powder, modified attapulgite and rare earth elements, put them into a ball rolling machine, spray water mist into the ball rolling machine to form primary particles first, and start the next step after the particles reach a particle size of 4 mm;

[0083] Step 3: Add the modified self-polarized composite material into the ball rolling machine, spray water mist into the ball rolling machine, and start the next step after the particles reach 7 mm;

[0084] Step 4: Dry the particles obtained in step 3 under natural conditions for 48 hours, then put them into an autoclave for steam curing at 180-200° C. for 20 hours, and dry them to obtain a negative oxygen ion functional particle ball.

[0085] Example 4

[0086] This embodiment provides a method for preparing negative oxygen ion functional granular balls

[0087] 1. Preparation of modified attapulgite:

[0088] S1. The waste attapulgite is placed in a muffle furnace for oxidation calcination at a temperature of 600° C. for 1 h, and then crushed with a high-speed universal crusher for 30 seconds and passed through a 100-mesh sieve to obtain oxidized attapulgite.

[0089] S2. Mix oxidized attapulgite, ethanol and deionized water in a mass ratio of 10:150:150, stir magnetically for 30 minutes, add a modifier, adjust the temperature to 60°C, stir with a constant temperature magnetic stirrer for 15 hours, filter after stirring, wash the filter residue with ethanol and deionized water, put it into an oven, and dry it at a temperature of 40-50°C for 60 minutes to obtain modified attapulgite.

[0090] 2. Preparation of modified self-polarized composite materials:

[0091] 1) Mixing bentonite, lithium carbonate and gypsum in a mass ratio of 20:10:30 to obtain a mixed material;

[0092] 2) adding the mixed material, zirconium oxide ball milling beads and water into a ball mill at a mass ratio of 1:1.5:0.7, and ball milling for 5 hours. The ball-milled material was placed in a forced air drying oven at 80°C for 24 hours to remove moisture from the mixed material, and passed through a 100-mesh sieve to obtain an intermediate 1;

[0093] 3) The intermediate 1 and polyvinyl pyrrolidone were added into a corundum crucible at a mass ratio of 1000:3, and calcined at 700° C. for 3 h to obtain a modified self-polarized composite material.

[0094] 3. Preparation of negative oxygen ion functional granular balls:

[0095] Step 1, weighing the modified self-polarized composite material, modified attapulgite, rare earth element, and tourmaline powder in a weight ratio of 45:30:15:30 for standby use;

[0096] Step 2: After mixing tourmaline powder, modified attapulgite and rare earth elements, put them into a ball rolling machine, spray water mist into the ball rolling machine to form primary particles first, and start the next step after the particles reach a particle size of 4 mm;

[0097] Step 3: Add the modified self-polarized composite material into the ball rolling machine, spray water mist into the ball rolling machine, and start the next step after the particles reach 5mm;

[0098] Step 4: Dry the particles obtained in step 3 under natural conditions for 24 hours, then put them into an autoclave for steam curing at 180° C. for 20 hours, and dry them to obtain a negative oxygen ion functional particle ball.

[0099] Example 5

[0100] This embodiment provides a method for preparing negative oxygen ion functional granular balls

[0101] 1. Preparation of modified attapulgite:

[0102] S1. The waste attapulgite is placed in a muffle furnace for oxidation calcination at a temperature of 550° C. for 2 h, and then crushed with a high-speed universal crusher for 15 seconds and passed through a 100-mesh sieve to obtain oxidized attapulgite.

[0103] S2. Mix oxidized attapulgite, ethanol and deionized water in a mass ratio of 10:150:150, stir magnetically for 30 minutes, add a modifier, adjust the temperature to 60°C, stir with a constant temperature magnetic stirrer for 12 hours, filter after stirring, wash the filter residue with ethanol and deionized water, put it into an oven, and dry it at 40°C for 60 minutes to obtain modified attapulgite.

[0104] 2. Preparation of modified self-polarized composite materials:

[0105] 1) Mixing bentonite, lithium carbonate and gypsum in a mass ratio of 20:10:30 to obtain a mixed material;

[0106] 2) adding the mixed material, zirconium oxide ball milling beads and water into a ball mill at a mass ratio of 1:1.7:0.5, and ball milling for 4-5 hours. The ball-milled material was placed in a forced air drying oven at 80°C for 18 hours to remove moisture from the mixed material, and passed through a 100-mesh sieve to obtain an intermediate 1;

[0107] 3) The intermediate 1 and polyvinyl pyrrolidone were added into a corundum crucible at a mass ratio of 1000:4, and calcined at 750° C. for 3 h to obtain a modified self-polarized composite material.

[0108] 3. Preparation of negative oxygen ion functional granular balls:

[0109] Step 1, weighing the modified self-polarized composite material, modified attapulgite, rare earth element, and tourmaline powder in a weight ratio of 50:35:20:20 for standby use;

[0110] Step 2: After mixing tourmaline powder, modified attapulgite and rare earth elements, put them into a ball rolling machine, spray water mist into the ball rolling machine to form primary particles first, and start the next step after the particles reach a particle size of 3 mm;

[0111] Step 3: Add the modified self-polarized composite material into the ball rolling machine, spray water mist into the ball rolling machine, and start the next step after the particles reach 7 mm;

[0112] Step 4: Dry the particles obtained in step 3 under natural conditions for 36 hours, then put them into an autoclave for steam curing at 180° C. for 22 hours, and dry them to obtain a negative oxygen ion functional particle ball.

[0113] Example 6

[0114] This embodiment provides a method for preparing negative oxygen ion functional granular balls

[0115] 1. Preparation of modified attapulgite:

[0116] S1. The waste attapulgite is placed in a muffle furnace for oxidation calcination at a temperature of 600° C. for 2 h, and then crushed with a high-speed universal crusher for 15 seconds and passed through a 100-mesh sieve to obtain oxidized attapulgite.

[0117] S2. Mix oxidized attapulgite, ethanol and deionized water in a mass ratio of 10:150:150, stir magnetically for 15 minutes, add a modifier, adjust the temperature to 60°C, stir with a constant temperature magnetic stirrer for 12 hours, filter after stirring, wash the filter residue with ethanol and deionized water, put it into an oven, and dry it at 45°C for 45 minutes to obtain modified attapulgite.

[0118] 2. Preparation of modified self-polarized composite materials:

[0119] 1) Mixing bentonite, lithium carbonate and gypsum in a mass ratio of 30:10:40 to obtain a mixed material;

[0120] 2) The mixed material, zirconium oxide ball milling beads and water were added into a ball mill at a mass ratio of 1:1.7:0.8, and the ball milled material was placed in a forced air drying oven at 90°C for 12 hours to remove moisture from the mixed material, and passed through a 100 mesh sieve to obtain an intermediate 1;

[0121] 3) The intermediate 1 and polyvinyl pyrrolidone were added into a corundum crucible at a mass ratio of 1000:3, and calcined at 750° C. for 3 h to obtain a modified self-polarized composite material.

[0122] 3. Preparation of negative oxygen ion functional granular balls:

[0123] Step 1, weighing the modified self-polarized composite material, modified attapulgite, rare earth element, and tourmaline powder in a weight ratio of 40:30:10:20 for standby use;

[0124] Step 2: After mixing tourmaline powder, modified attapulgite and rare earth elements, put them into a ball rolling machine, spray water mist into the ball rolling machine to form primary particles first, and start the next step after the particles reach a particle size of 3 mm;

[0125] Step 3: Add the modified self-polarized composite material into the ball rolling machine, spray water mist into the ball rolling machine, and start the next step after the particles reach 5mm;

[0126] Step 4: Dry the particles obtained in step 3 under natural conditions for 48 hours, then put them into an autoclave for steam curing at 180° C. for 24 hours, and dry them to obtain a negative oxygen ion functional particle ball.

[0127] Comparative Example 1

[0128] This comparative example provides a method for preparing negative oxygen ion functional granular balls

[0129] The difference between this comparative example and Example 1 is that no modified attapulgite is prepared in this comparative example.

[0130] 1. Crush the waste attapulgite with a high-speed universal grinder for 15 seconds, wash it with deionized water, and pass it through a 100-mesh sieve to obtain attapulgite;

[0131] 2. Preparation of modified self-polarized composite materials:

[0132] 1) Mixing bentonite, lithium carbonate and gypsum in a mass ratio of 30:10:40 to obtain a mixed material;

[0133] 2) The mixed material, zirconium oxide ball milling beads and water were added into a ball mill at a mass ratio of 1:1.2:0.8, and the ball milled material was placed in a forced air drying oven at 90°C for 12 hours to remove moisture in the mixed material, and passed through a 100 mesh sieve to obtain an intermediate 1;

[0134] 3) The intermediate 1 and polyvinyl pyrrolidone were added into a corundum crucible in a mass ratio of 1000:3, and calcined at 700° C. for 4 h to obtain a modified self-polarized composite material.

[0135] 3. Preparation of negative oxygen ion functional granular balls:

[0136] Step 1, weighing the modified self-polarized composite material, attapulgite, rare earth element, and tourmaline powder in a weight ratio of 40:30:10:20 for standby use;

[0137] Step 2: After mixing tourmaline powder, attapulgite and rare earth elements, put them into a ball rolling machine, spray water mist into the ball rolling machine to form primary particles first, and start the next step after the particles reach a particle size of 3 mm;

[0138] Step 3: Add the modified self-polarized composite material into the ball rolling machine, spray water mist into the ball rolling machine, and start the next step after the particles reach 5mm;

[0139] Step 4: Dry the particles obtained in step 3 under natural conditions for 24 hours, then put them into an autoclave for steam curing at 200° C. for 24 hours, and dry them to obtain a negative oxygen ion functional particle ball.

[0140] Test Example 1

[0141] Eight test chambers with the same formaldehyde concentration were set up and divided into seven experimental groups and one control group. The same mass of a negative oxygen ion functional granular ball prepared in Examples 1 to 6 and Comparative Example 1 was added to the seven experimental groups respectively. No air purification treatment was performed in the control group, and the formaldehyde concentration was measured and recorded at regular intervals.

[0142] Table 1 is a test table of the formaldehyde adsorption efficiency of a negative oxygen ion functional granular ball prepared in Examples 1 to 6 and Comparative Example 1 in Test Example 1

[0143]

[0144] It can be seen from Table 1 that after each detection of the formaldehyde adsorption efficiency, the detection efficiency of Examples 1 to 6 is higher than that of Comparative Example 1, indicating that the modified attapulgite can improve the adsorption efficiency of the negative oxygen ion functional granules for formaldehyde.

[0145] The tourmaline powder used in Examples 1 to 6 and Comparative Example 1 comes from Lingshou County Dexu Mining Co., Ltd., with a product number of dqskl and a purity of 99%; the lithium carbonate used comes from Henan Xiangfa Chemical Products Co., Ltd., with a CAS number of 5248-9841 and a purity of 99.3%.

[0146] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A negative oxygen ion functional granular ball, characterized in that: Includes surface materials and internal materials; Wherein, the surface layer material comprises a modified self-polarized composite material.

2. The negative oxygen ion functional granular ball according to claim 1, characterized in that: The internal material comprises a mineral material with permanent electrodes and an ultra-fine mesh mineral clay; Wherein, the mineral material with permanent electrodes is tourmaline powder; The modified self-polarized composite material is prepared by mixing bentonite, lithium carbonate and gypsum.

3. The negative oxygen ion functional granular ball according to claim 1, characterized in that: The ultrafine mineral clay comprises modified attapulgite and rare earth elements; Wherein, the rare earth element is at least one of cerium oxide, neodymium oxide and lanthanum oxide.

4. The negative oxygen ion functional granular ball according to claim 3, characterized in that: The modified attapulgite is prepared by mixing oxidized attapulgite and a modifier; The oxidized attapulgite is prepared by oxidizing and calcining discarded attapulgite in a muffle furnace.

5. The negative oxygen ion functional granular ball according to claim 3, characterized in that: The modifier comprises at least one of octadecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide and phenyltripropylammonium bromide.

6. A method for preparing negative oxygen ion functional granular balls, characterized in that: The following steps are involved: Step 1, prepare materials: weigh the modified self-polarized composite material, modified attapulgite, rare earth element, and tourmaline powder in a weight ratio of 40-50:30-40:10-20:20-30 and set aside; Step 2: After mixing tourmaline powder, modified attapulgite and rare earth elements, put them into a ball rolling machine, spray water mist into the ball rolling machine to form primary particles first, and start the next step after the particles reach a particle size of 3 to 4 mm; Step 3: Add the modified self-polarized composite material into the ball rolling machine, spray water mist into the ball rolling machine, and start the next step after the particles reach 5-7 mm; Step 4: Dry the particles obtained in step 3 under natural conditions for 24 to 48 hours, then put them into an autoclave for steam curing at 180 to 200° C. for 20 to 24 hours, and dry them to obtain a negative oxygen ion functional particle ball.

7. The method for preparing a negative oxygen ion functional granular ball according to claim 6, characterized in that: The preparation method of the modified self-polarized composite material is as follows: 1) Mixing bentonite, lithium carbonate and gypsum in a mass ratio of 20-30:10:30-40 to obtain a mixed material; 2) adding the mixed material, zirconium oxide ball milling beads and water into a ball mill at a mass ratio of 1:1.2-1.7:0.5-0.8, and ball milling for 4-5 hours. The ball-milled material is placed in a forced air drying oven at 70-90° C. for 12-24 hours to remove moisture from the mixed material, and passed through a 100-mesh sieve to obtain an intermediate 1; 3) adding the intermediate 1 and polyvinyl pyrrolidone into a corundum crucible at a mass ratio of 1000:3-5, and calcining at 700-750° C. for 3-4 hours to obtain a modified self-polarized composite material.

8. The method for preparing a negative oxygen ion functional granular ball according to claim 6, characterized in that: The preparation method of the modified attapulgite is as follows: S1, placing the waste attapulgite in a muffle furnace for oxidation calcination at a temperature of 550-600° C. for 1-2 h, then crushing it with a high-speed universal crusher for 15-30 seconds, passing it through a 100-mesh sieve, and obtaining oxidized attapulgite; S2. Mix oxidized attapulgite, ethanol and deionized water in a mass ratio of 10:150-200:150-200, stir magnetically for 15-30 min, add a modifier, adjust the temperature to 60°C, stir with a constant temperature magnetic stirrer for 12-15 h, filter after stirring, wash the filter residue with ethanol and deionized water, put it into an oven, and dry it at 40-50°C for 30-60 min to obtain modified attapulgite.

9. An application of the negative oxygen ion functional granular ball according to claim 1 in purifying indoor air and purifying the air in a car.

10. A use according to claim 9, characterized in that: The reaction process of the negative oxygen ion functional granules in the application to ionize negative ions in the air is: H2O→OH - +H + <h2 style=";text-align:left;direction:ltr">2H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> +2e<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> →H2 OH - +H2O→H30 - O2+e - →O2 - 。